A extensão rural pública e o perfil dos extensionistas do Centro de Desenvolvimento Agropecuário de Concepción - Paraguai - Mendoza, Benito Armando Solis (2009)
The present study describes as the objectives of Public Rural Extension in Paraguay and the extensionist profile in the Departament of Concepcion and Amambay. To reach the objectives a case study format was employet with a questonaire containing open-ended questions used to explore the metodhology of work of extension in the field and the extension agent profile. The study also includes a basic background of local extension agents in the area selected. It is concluded that the service of public extension is carried out in a deficient way due to the structural conditions (mainly lack of resources) that affect the service, and, as a result, the attitude and motivation of the extension agents working in the ACD. At the end some suggestions are presented to improve the situation.